2011
DOI: 10.4103/0970-0218.86520
|View full text |Cite
|
Sign up to set email alerts
|

A study on consciousness of adolescent girls about their body image

Abstract: Background:Perceived body image is an important potential predictor of nutritional status. Body image misconception during adolescence is unexplored field in Indian girls.Objectives:To study the consciousness of adolescent girls about their body image.Materials and Methods:This multistage observational study was conducted on 586 adolescent girls of age 10–19 years in Lucknow district (151 from rural, 150 from slum, and 286 from urban area) of Uttar Pradesh, India. Information on desired and actual body size wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…[ 23 ] In Lucknow, 73.4% adolescent girls were satisfied with their body image, while 26.6% were dissatisfied. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] In Lucknow, 73.4% adolescent girls were satisfied with their body image, while 26.6% were dissatisfied. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…For most female patients with adolescent idiopathic scoliosis (AIS) the perspective of body deformity is a matter of special concern. Patients observe physical changes in their bodies closely and compare themselves to adolescents without scoliosis, therefore a negative self-evaluation of appearance may lead to different reactions concerning body shape such as body dissatisfaction, negative body image, concern over body size and shape (Dixit et al 2011 ). It must be emphasized that adolescence is a period which is especially vulnerable to disturbances in female body image, since in Western societies greater importance of appearance is observed among females (Davison and McCabe 2006 ; Wardle and Foley 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Swati Dixit et al, showed that 73.4% were satisfied with their current body size, and among those satisfied 32.8% were under weight and 38.4% were stunted. 4.9% under estimated their weight and 32.8% over estimated [18]. It was seen that urban subjects were more dissatisfied than their rural and slum counterparts.…”
Section: Original Research Articlementioning
confidence: 87%